Teacher Diversity in Canada: Leaky Pipelines, Bottlenecks, and Glass Ceilings - Ryan, James; Pollock, Katina; Antonelli, Fab (Canadian Journal of Education/Revue canadienne de l’éducation, 2009)
This article examines the racial diversity of the teacher population in Canada. In particular, we compare the number of teachers of colour in Canadian elementary and secondary schools from the 2001 and 2006 Census data with the diversity of the student and general populations. We also explore ways to understand the gap between the proportion of Cana‐ dian educators and students of colour by interrogating the leaky pipeline metaphor that scholars commonly employ to account for labour shortages. We contend that the pipeline metaphor, frequently used to account for supply and demand balances in various profes‐ sions, does not sufficiently explain this disparity, and we explore others. Key words: diversity, teacher workforce, equity, metaphor Les auteurs se penchent sur la diversité raciale d’effectif enseignant au Canada. Ils exami‐ nent en particulier le nombre d’enseignants de couleur dans les écoles primaires et se‐ condaires canadiennes selon les données de recensement de 2001 et de 2006 et les compa‐ rent à la diversité raciale de la population scolaire et de la population en général. Cet arti‐ cle explore en outre les façons de comprendre l’écart entre la proportion d’enseignants et d’élèves de couleur en analysant la métaphore du pipeline qui fuit souvent employée par les universitaires pour expliquer les pénuries de main‐d’œuvre. Les auteurs soutiennent que cette métaphore, fréquemment utilisée pour rendre compte des déficits entre l’offre et de la demande dans diverses professions, ne suffit pas à expliquer la disparité observée et proposent d’autres métaphores. Mors clés : diversité, effectif enseignant, équité